Chaos engineering observability : bringing chaos experiments into system observability - Miles, Russ (O'Reilly Media, 2019)
Chaos engineering is a highly collaborative activity. When applied well, virtually everyone is responsible for exploring, surfacing, overcoming, and validating weaknesses in their systems. That can lead to a lot of chaos engineering activity across a collection of systems at any moment in time. How can you keep chaos engineering from becoming, well, too chaotic? One key technique is chaos observability. In this ebook, Russ Miles of ChaosIQ demonstrates how to bring your chaos experiments into the world of system observability. Chaos observability enables you to surface, debug, and even visualize chaos experiment activities across your system in real time and through time series recordings. You'll learn how chaos observability helps everyone in production be aware of chaos activities occurring within and across systems. Understand why it's imperative to make chaos engineering observable Learn how to bring chaos experiments and engineering into the overall system observability picture Make chaos observability actionable and difficult to ignore through alerts and Slack integration.